Design and Construction of Foundations in Areas of Deep Seasonal Frost and Permafrost. - Linell,Kenneth A; Lobacz,Edward F (1980)
This report presents engineering guidance for the design and construction of foundations in areas of deep seasonal frost and permafrost as developed up to the early 1970's. Attention is given to basic considerations affecting foundation design, site investigations, survey datum points, construction consideration, and monitoring performance. Included in the main text are 17 tables, 141 figures, and 213 selected references. A bibliography presents 45 additional references.